2019 IEEE Information Theory Workshop (ITW) 2019
DOI: 10.1109/itw44776.2019.8989359
|View full text |Cite
|
Sign up to set email alerts
|

Density Evolution Analysis of Partially Information Coupled Turbo Codes on the Erasure Channel

Abstract: In this paper, we investigate the performance of a class of spatially coupled codes, namely partially information coupled turbo codes (PIC-TCs) over the binary erasure channel (BEC). This class of codes enjoy flexible code rate adjustment by varying the coupling ratio. Moreover, the coupling method can be directly applied to any component codes without changing the encoding and decoding architectures of the underlying component codes. However, the theoretical performance of PIC-TCs has not been fully investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Both theoretical analysis and simulation results in [21], [24] showed that partiallycoupled turbo codes outperform SC-PCCs and have comparable performance to SC-SCCs and SC-BCCs. However, threshold saturation was neither observed nor proven for PIC-TCs in [18], [20], [21], [24].…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Both theoretical analysis and simulation results in [21], [24] showed that partiallycoupled turbo codes outperform SC-PCCs and have comparable performance to SC-SCCs and SC-BCCs. However, threshold saturation was neither observed nor proven for PIC-TCs in [18], [20], [21], [24].…”
mentioning
confidence: 88%
“…Theorem 1. For the spatially-coupled system defined in (20) and any < c , where c is the potential threshold associated with the potential function in (14), the only fixed point of the recursion in ( 20) is x = 0 as L → ∞, m → ∞ and L m.…”
Section: A Threshold Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark: We compare the construction of the PIC-dTCs with that of the PIC-TCs [9], [13]. For the PIC-TCs with TC1 as component code, the CB encoder only has one information sequence.…”
Section: Encoding Of Pic-dtcs With Coupling Memory M ≥mentioning
confidence: 99%
“…However, due to the coupling, (i.e., the same information sharing between CBs), PIC codes have significant rate loss compared to its component codes. For example, in [9], [13], with a rate- 1 3 turbo code as component code, the PIC-TC ensembles have a code rate of 1 5 when half of the information bits are coupled.…”
Section: Introductionmentioning
confidence: 99%